An investigation into the relationship between kinesthetic sensitivity and balancing ability in pre-school children - Burger, Laetitia Mary (Rhodes University, Faculty of Education, Department of Education, 1991)
The purpose of this study was to explore the possibility of a linear relationship between kinesthetic sensitivity and balancing ability in pre-school children. Furthermore, the effects of age on kinesthetic sensitivity and balancing ability were investigated. Finally, the role of gender in kinesthetic sensitivity and balancing ability was examined. Fifty-one subjects, between the ages of three and six years, executed five trials on each of two kinesthetic sensitivity tests (an arm abduction test and a hip abduction test); two tests for static balance (on a balance board and on a balance stick) and two tests for dynamic balance (a beam walk test and a stepping stones test). Although the correlations between kinesthetic sensitivity and balancing ability were generally positive, they were very slight. These low correlations are probably an indication that different abilities are required for carrying out the different tasks. Generally, both balancing ability and kinesthetic sensitivity appeared to improve with age. From analysis of individual test results it was obvious that abilities varied from individual to individual (Appendix G). This could have been the result of developmental, motivational or experiential differences. Although the girls generally performed slightly better on most tests than the boys the correlations between test scores for boys were slightly higher than those for girls. At-test indicated that there were no significant differences between the mean scores of the boys and the girls on the balancing or the kinesthetic sensitivity tasks.
Keywords: Motor ability in children; Perception in children; Preschool children